THE ROLE OF LITERATURE IN LANGUAGE LEARNING - Subkhonov Shermurod Sherqulovich (Web of Journals Publishing, 2025)
The role of literature in language learning is incomparable. In the deep and complete acquisition of any language, it is necessary to get acquainted not only with the wealth of grammatical rules and vocabulary, but also with culture, history and the worldview of the people. Literature, on the other hand, is an important tool that unites exactly this trinity, enlivening the language and allowing it to be used in life situations. Referring to literature in the language learning process teaches the reader not only to learn new words and expressions, but also to use them correctly in context.
Keywords: Literature, language, context, style, genre, educational materials, culture, drama.